Decarbonizing Saudi Arabia energy and industrial sectors: Assessment of carbon capture cost - Feras Rowaihy; Ali Hamieh; Naser Odeh; Mohamad Hejazi; Mohammed Al-Juaied; Abdulkader M. Afifi; Hussein Hoteit (Carbon Capture Science & Technology)
The global drive for net-zero emissions has highlighted carbon capture, utilization, and storage (CCUS) as a critical tool to reduce CO₂ emissions from energy and industrial sectors. Achieving climate goals necessitates a comprehensive understanding of regional CO₂ emission profiles and capture costs to inform effective decarbonization strategies. As one of the largest CO₂ emitters globally, Saudi Arabia has committed to achieving net-zero emissions by 2060. However, the economic implications of deploying CCUS within the Kingdom remain insufficiently explored. This work provides updated estimates of CO₂ emissions across key sectors in Saudi Arabia, including electricity, petrochemicals, refineries, cement, steel, ammonia production, and desalination, based on 2022 data. The CO2 capture costs are estimated by incorporating stationary emission plant data with reference cases from analogous industrial sectors, including capital expenditure (CAPEX) and operating expenditure (OPEX). The total capture cost per ton of CO2 is determined by combining these cost components using an established economic model and a custom-developed tool. The study constructs a comprehensive CO₂ capture cost curve for Saudi Arabia, highlighting the variability of capture costs across regions and industries. Our analysis indicates an average CO₂ capture cost of $69/tCO₂, with substantial variability across industries. Ammonia production emerges as the most cost-efficient at $11/tCO₂, driven by its high CO₂ concentration, whereas smaller-scale operations can incur costs up to $189/tCO₂. Results show that economies of scale and CO₂ concentration play pivotal roles in determining capture feasibility, with low-cost opportunities identified in ammonia production and high-emission industrial clusters, particularly in the Eastern and Western regions. The Eastern region, with its planned CCS hub in Jubail, emerges as the most promising for near-term deployment. In contrast, the Western region requires additional focus on storage alternatives such as mineralization. Benchmarking against global capture costs reveals that Saudi Arabia's industrial landscape, characterized by large-scale emitters, is well-positioned for cost-effective CCUS implementation. The study highlights the need to prioritize low-cost capture opportunities and develop strategies tailored to regional and sector-specific conditions, offering a roadmap for the Kingdom's significant contribution to global net-zero ambitions.